Philosophical and Psychological Foundations ofthe Hereafter in the Context of Desire For Immortality - Abuzarova, Ulkar (Scholarya Demo Journal of Ruby, 2019)
The issue of the Hereafter has multifaceted dimensions and linked tophilosophical thought and parapsychological data. Therefore, the Hereafter, asone of the most debated topics on metaphysics is always up to date. In thissense, a study of religious and philosophical foundations of the Hereafter is ofgreat importance. This article focuses on the alleged evidences of the possibility and necessity of the Hereafter in the context of desire for immortality. This topic was analyzed from the standpoint of Islamic and Western theologians-philosophers. This article examines both the evidences that base on psychological aspects and their criticism. It has been shown that both Islamic and some Western scholars advocate the belief of the Hereafter by arguing for the desire for immortality onthe philosophical-psychological basis. This research also lays out that the desire for immortality that is universal desire is expressed in various ways in the platform of belief and thought. In this sense, besides metaphysical and physical immortality, social and biological immortality are also examined in the contextof philosophy. Finally, the article analyzes the arguments of the thinkers such as John Stuart Mill, Dugald Stewart and David Hume, who belief that it isimpossible for the necessity of the Hereafter to rest on the desire for immortality which is inherently exist in human nature.